The Role of Social Media in Shaping the Brand Image: A Field Study on the Iraqi Audience - خضر ايلاف قصي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The study aims to identify the role of social media in shaping the brand image among the Iraqi audience. A descriptive methodology was applied using a questionnaire tool on a sample of 94 participants. The study concluded with results indicating that social media platforms play an important role in shaping public opinion. It showed that Facebook, Twitter, and Instagram play a vital role in forming the Iraqi audience’s views on brands. Sixty percent of participants confirmed that social media significantly affects their perception of brands. The results also revealed that the quality of content and audience interaction are critical factors in the success of brands on these platforms. The study found that 45% of participants believe that the platforms need improvement to make them more attractive and relevant to their interests. Focusing on improving digital content and increasing effective customer interaction.